Transient Magnetothermal Neuronal Silencing Using the Chloride Channel Anoctamin 1 (TMEM16A) - Munshi, Rahul; Qadri, Shahnaz M.; Pralle, Arnd (Frontiers in Neuroscience, 2018)
The importance of specific neurons to a network’s function is best studied by precisely timed, reversible silencing of these neurons. Previously, we have shown that alternating magnetic field mediated heating of magnetic nanoparticles, bound to neurons, expressing temperature-sensitive cation channels TRPV1 remotely activates these neurons, evoking behavioral responses in mice. Here, we demonstrate how to apply magnetic nanoparticle heating to silence target neurons. Rat hippocampal neuronal cultures were transfected to express the temperature gated chloride channel, Anoctamin1 (TMEM16A). Spontaneous firing was suppressed within seconds of alternating magnetic field application to Anoctamin1 (TMEM16A) channel expressing, magnetic nanoparticle decorated neurons. Five seconds of magnetic field application leads to about 12 seconds of silencing, with a latency of about 2 seconds and an average suppression ratio of more than 80%. Immediately following the silencing period spontaneous activity resumed. The method provides a promising avenue for tether free, remote, transient neuronal silencing in vivo for both scientific and therapeutic applications.